2018
DOI: 10.1155/2018/3061742
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Water: An Unexpected Source of Urinary Citrate

Abstract: Purpose Coconut water has long been touted for its medicinal qualities including natural hydration. We sought to determine whether its consumption would induce changes to urinary lithogenic factors beyond changes in urine volume. Materials and Methods After Institutional Review Board approval, volunteers with no prior history of nephrolithiasis were recruited. Each participant was randomized initially to either the coconut water or the water phase of the study. Participants kept meticulous food and fluid intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…18,19 Aside from lemon-and orange-based beverages, other drinks, including grapefruit juice and coconut water, have shown similar changes in urinary citrate and pH after controlled consumption in healthy volunteers. 11,12 Compared with controls, after 4-7 days of grapefruit juice or coconut water consumption, urinary pH and citrate did increase, but these changes were all nonsignificant except for the increase in urinary citrate concentration after coconut water consumption (Table 4). By comparison, all beverage trials that used OJ (including this study for pH) showed statistical increases in urinary pH and citrate after 7 days of consumption (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…18,19 Aside from lemon-and orange-based beverages, other drinks, including grapefruit juice and coconut water, have shown similar changes in urinary citrate and pH after controlled consumption in healthy volunteers. 11,12 Compared with controls, after 4-7 days of grapefruit juice or coconut water consumption, urinary pH and citrate did increase, but these changes were all nonsignificant except for the increase in urinary citrate concentration after coconut water consumption (Table 4). By comparison, all beverage trials that used OJ (including this study for pH) showed statistical increases in urinary pH and citrate after 7 days of consumption (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 93%
“…6 In addition, lemon-based beverages have been evaluated extensively in both bench 7 and clinical settings. [8][9][10] Changing urinary citrate and pH levels with concentrated lemon extract, lemonade, grapefruit, 11 raspberry, and coconut juice 12 have had mixed results. Despite early evidence that OJ harbored excellent alkali potential, valid concerns over the sugar content in OJ, in combination with the promising bench results of concentrated lemon juice, led to a focused effort evaluating the efficacy of lemon-based beverages on urinary citrate and pH modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the relative risk of calcium oxalate stone formation was unaffected [70,72] or reduced [71] in healthy volunteers but increased in stone patients after the intake of cranberry juice [72]. Finally, a study of healthy subjects showed that the consumption of 1.9 L/day of coconut water compared to tap water significantly raised urinary citrate, potassium, and chloride excretion, without affecting urine pH [73]. Although fruit and vegetable juices could be useful in the dietary therapy of kidney stone disease, the oxalate concentration has to be taken into account.…”
Section: Fruit Juices and Fruit Juice Beveragesmentioning
confidence: 96%
“…16,17 Coconut water, due to a large malate as alkali component, can also increase urinary citrate if ingested in large quantities. 18 In addition, some citrus-flavored carbonated beverages also contain large portions of alkali due to citrate and malate content, however, substantial volumes of these beverages would need to be ingested to match the alkali content of prescribed potassium citrate. 19…”
Section: Urinary Alkalizationmentioning
confidence: 99%